2002
DOI: 10.1242/dev.129.16.3783
|View full text |Cite
|
Sign up to set email alerts
|

TheIIIcalternative ofFgfr2is a positive regulator of bone formation

Abstract: Fibroblast growth factor receptor type 2 (FGFR2) plays major roles in development. Like FGFR1 and FGFR3, it exists as two splice variants, IIIb and IIIc. We have investigated in the mouse the function of FGFR2IIIc, the mesenchymal splice variant of FGFR2. Fgfr2IIIc is expressed in early mesenchymal condensates and in the periosteal collar around the cartilage models; later it is expressed in sites of both endochondral and intramembranous ossification. A translational stop codon inserted into exon 9 disrupted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 232 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Fgfr2 is subject to AS that produces tissue-specific isoforms depending on the inclusion of exon 8 (epithelial 'b' isoforms) or exon 9 (mesenchymal 'c' isoforms). Both isoforms are required for proper craniofacial development (De Moerlooze et al, 2000;Eswarakumar et al, 2002). Analysis of Fgfr2 expression from RNA isolated from the facial processes of E12.5 control and cKO embryos revealed that both epithelia-and mesenchyme-specific splice isoforms were observed in each genotype (Fig.…”
Section: Srsf3 Regulates the Alternative Rna Splicing Of Transcripts ...mentioning
confidence: 97%
“…Fgfr2 is subject to AS that produces tissue-specific isoforms depending on the inclusion of exon 8 (epithelial 'b' isoforms) or exon 9 (mesenchymal 'c' isoforms). Both isoforms are required for proper craniofacial development (De Moerlooze et al, 2000;Eswarakumar et al, 2002). Analysis of Fgfr2 expression from RNA isolated from the facial processes of E12.5 control and cKO embryos revealed that both epithelia-and mesenchyme-specific splice isoforms were observed in each genotype (Fig.…”
Section: Srsf3 Regulates the Alternative Rna Splicing Of Transcripts ...mentioning
confidence: 97%
“…4 A ). For example, FGFR2 , which is expressed in the limb ectoderm, apical ectodermal ridge, skeletal anlagen, perichondrium, and periosteum, is necessary for limb formation, with loss of isoform FGFR2 IIIc or gain-of-function mutations in FGFR2 resulting in shortened limbs and digits ( 17 , 18 ). Furthermore, FBN2 knockout mice have shorter limb bones than wild-type mice ( 19 ).…”
Section: Resultsmentioning
confidence: 99%
“…FGFs are also often mentioned as a candidate [79], but there is no evidence for the colocalization of their signal with condensations. Although an FGF receptor, Fgfr2 (more precisely its IIIc isoform) is expressed in the prechondrogenic mesenchyme [89,90], the loss of Fgfr2 in the limb mesenchyme affects only a minor growth defect [91]. Similarly, no patterning defects are also observed in the limbs lacking galectins (e.g., [92]), which were proposed as Turing molecules to explain digit patterning in chick embryos.…”
Section: Intertwining the Turing Mechanism And Positional Information...mentioning
confidence: 99%